2014
DOI: 10.1108/ijse-11-2012-0223
|View full text |Cite
|
Sign up to set email alerts
|

Economic risk analysis of alternative farming systems for smallholder farmers in central and north-east Thailand

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Stochastic dominance and stochastic efficiency with respect to a function (SDRF and SERF) analyses have a major advantage in that they reduce the set of all possible risky choices to a small group of alternatives. The SERF technique is a novel improved methodology for assessing and ranking risky alternatives but empirical studies using SERF are limited, Especially in agriculture, SDRF and SERF analyses have been used to compare risky alternatives regarding farm production, marketing and financial matters [11]. In Greece, SERF analysis has been used by Tzouramani et al [12] to determine risk efficiency between organic and conventional lemons and citrus cultivation and by Tzouramani et al [13], to explore the economic viability of conventional and organic sheep farming.…”
Section: Methodsmentioning
confidence: 99%
“…Stochastic dominance and stochastic efficiency with respect to a function (SDRF and SERF) analyses have a major advantage in that they reduce the set of all possible risky choices to a small group of alternatives. The SERF technique is a novel improved methodology for assessing and ranking risky alternatives but empirical studies using SERF are limited, Especially in agriculture, SDRF and SERF analyses have been used to compare risky alternatives regarding farm production, marketing and financial matters [11]. In Greece, SERF analysis has been used by Tzouramani et al [12] to determine risk efficiency between organic and conventional lemons and citrus cultivation and by Tzouramani et al [13], to explore the economic viability of conventional and organic sheep farming.…”
Section: Methodsmentioning
confidence: 99%
“…, 2021; Rizwan et al. , 2020; Aditto, 2011). A systematic review of farmers' perception of agricultural risks found climate change, human and market risks to be the most feared risk in the crop sector (Duong et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Extant literature has found age, gender, educational level and farming experience, farm size and off-farm work to have a significant influence on farmers' perceived source of agricultural risks (Il Islam et al, 2021;Rizwan et al, 2020;Aditto, 2011). A systematic review of farmers' perception of agricultural risks found climate change, human and market risks to be the most feared risk in the crop sector (Duong et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Penerimaan merupakan hasil kali produksi total benih ikan nila merah dengan harga produk ikan nila merah sesuai dengan ukurannya Berikut merupakan biaya total, rata-rata penerimaan dan pendapatan pada pembenihan ikan nila merah di KPI Mino Ngemboko : Identifikasi Sumber-sumber Risiko Pembenihan Ikan Nila Merah Pembudidaya dalam menjalankan pembenihan ikan nila merah tentunya tidak terlepas dari berbagai permasalahan. Pembudidaya selalu menghadapi risiko di dalam usahanya, terutama karena kebanyakan hasil pertanian masih bergantung pada musim dan cuaca seperti di negara-negara lain India (Kumar dan Singh, 2017), Thailand (Aditto, 2011), Estonia (Laanemets, 2011) termasuk juga pembenihan ikan nila merah masih bergantung dengan alam. Beberapa sumber risiko yang terjadi saling berhubungan dan tidak bisa dipisah satu sama lain.…”
Section: Pengukuran Biaya Total Penerimaan Dan Pendapatan Budidaya Pembenihan Ikan Nila Merahunclassified